Conceptualizing Bilingual Education Programs through CLIL and Genre-Based Approach: An Indonesian Context - Yogi Saputra Mahmud (Universitas Hamzanwadi, 2020)
The implementation of bilingual education programs in the Indonesian secondary school context has experienced considerable changes in the last decade. In this case, the enactment of the International Standards School (ISS) program that propelled the students to experience bilingual education programs at schools was discontinued by the government in 2015. Consequently, the discontinuation of the ISS program leads to the scarcity of studies in examining the progress and effectiveness of bilingual education programs in Indonesia. At the same time, the phenomenon of private schools that offer bilingual programs has been significantly more popular after the ISS program was abolished. However, there is a lack of established instruction on how to implement bilingual programs in such schools. Therefore, this paper aims to conceptualise the implementation of bilingual education programs through the implementation of Content and Language Integrated Learning (CLIL) and Genre-Based Approach (GBA). Drawing on the relevant literature, this paper examines a new perspective in bilingual education programs by considering the suitability between CLIL and genre theory in the Indonesian secondary school context. Further, this paper also provides a unit of work/syllabus sample that incorporates both CLIL and GBA. Ultimately, future implications in responding to the enactment of bilingual education programs in Indonesia are also discussed.